Involvement of Leishmania Phosphatases in Parasite Biology and Pathogeny - Freitas-Mesquita, Anita Leocadio; Dos-Santos, André Luiz Araújo; Meyer-Fernandes, José Roberto (Frontiers in Cellular and Infection Microbiology, 2021)
In the Leishmania lifecycle, the motile promastigote form is transmitted from the sand fly vector to a mammalian host during a blood meal. Inside vertebrate host macrophages, the parasites can differentiate into the amastigote form and multiply, causing leishmaniasis, one of the most significant neglected tropical diseases. Leishmania parasites face different conditions throughout their development inside sand flies. Once in the mammalian host, the parasites have to overcome the microbicide repertoire of the cells of the immune system to successfully establish the infection. In this context, the expression of protein phosphatases is of particular interest. Several members of the serine/threonine-specific protein phosphatase (STP), protein tyrosine phosphatase (PTP), and histidine acid phosphatase (HAcP) families have been described in different Leishmania species. Although their physiological roles have not been fully elucidated, many studies suggest they have an involvement with parasite biology and pathogeny. Phosphatases play a role in adaptation to nutrient starvation during parasite passage through the sand fly midgut. They are also important to parasite virulence, mainly due to the modulation of host cytokine production and impairment of the microbiocidal potential of macrophages. Furthermore, recent whole-genome expression analyses have shown that different phosphatases are upregulated in metacyclic promastigotes, the infective form of the mammalian host. Leishmania phosphatases are also upregulated in drug-resistant strains, probably due to the increase in drug efflux related to the activation of ABC transporters. Throughout this review, we will describe the physiological roles that have been attributed to Leishmania endogenous phosphatases, including their involvement in the adaptation, survival, and proliferation of the parasites inside their hosts.